Rancangan Sump Berdasarkan Arah Kemajuan Tambang - Dedy Jupiter Sihombing; Noveriady, Noveriady; Yunida Iashania (Pusat riset dan Inovasi Nasional, 2025)
A sump is a water reservoir that functions to accommodate runoff water in the pit before the water is pumped. This study was conducted to determine the location plan and sump capacity based on the direction of mine progress and the actual estimation of runoff discharge that enters the pit at PT. Wahyu Murti Garuda Kencana, Central Kalimantan. There is a water problem that interferes with production activities because the actual sump dimensions are insufficient to accommodate the daily discharge of water that enters the sump. So that the impact on the mining front is flooded or there is waterlogging that disrupts mining activities. The progress of the mine is directed towards the north of the sump so that the distance and dimensions of the actual sump are ineffective and unable to accommodate the incoming water discharge in accordance with the direction of the mine progress due to the mining location in the pit which is easily submerged by water. The drainage condition at PT. Wahyu Murti Garuda Kencana uses the mine dewatering method which is a method of removing water that flows into the mining sump using a pump. Theoretically, by conducting direct research on the sump area of PT. Wahyu Murti Garuda Kencana, the actual sump dimensions are insufficient to accommodate the water discharge that enters the pit. The design carried out pays attention to the mining plan so that the sump design to be designed can be applied in the field in accordance with the mine design. The shape of the sump designed is a trapezoidal shape with dimensions of 80 m x 70 m cross-section, 74 m x 64 m bottom section, depth of 4 m and 55 degree tilt angle and a total sump volume capacity of 20,672 m3.